Student Perceptions On Online Learning During The Covid-19 Pandemic For Social Science Subjects At SMP Negeri 6 Samarinda - Norma Wijayanti; Sudarman Sudarman; Vitria Rahayu (Educational Studies: Conference Series, 2021)
This research is motivated by the learning process that has changed from face-to-face learning in class to online learning during the COVID-19 pandemic. The purpose of this study was to explore student attitudes that were adjusted from several dimensions, namely online learning conditions, teaching materials, student interaction, learning styles and environment/accessibility as well as to determine student perceptions of online learning during the covid-19 pandemic, especially social studies subjects at SMP Negeri 6 Samarinda. The type of research used in this thesis is a case study with a qualitative approach. The data sources in this study were 5 students of class IX and 2 teachers of social studies subjects, with the sampling technique used was purposive sampling technique, while the data collection techniques in this thesis research used interview techniques, questionnaires and documentation. The results of this study indicate that the dimensions of online learning conditions consist of learning tools, namely mobile phones (96.5%), learning applications namely Google Classroom (85.1%) and online learning constraints, namely difficult internet networks (57%). Judging from the dimensions of the environment/accessibility, the environment is very supportive (72.8%) and from the learning atmosphere, students prefer to return to school face-to-face (71.1%). In addition, it can also be seen from the dimensions of student interaction in the form of semi-two-way interactions (78.1%), the dimensions of learning styles in the form of visual styles (89.5%), and the dimensions of teaching materials carried out during the online learning process are more assignments individual (86.8%). The conclusion of this study shows that there are still many obstacles in the implementation of online learning, and in terms of student attitudes there are still students who are not disciplined when carrying out online learning.